Wilms tumor in children: A multivariate analysis of prognostic factors, with emphasis on inferior vena cava/right atrium extension. Results from a single-center study. (February 2023) - Brener, Pedro Zanetta; Tannuri, Ana Cristina Aoun; Teixeira, Roberto Augusto Plaza; Cristofani, Lilian Maria; Evangelista, Ana Beatriz Rabelo; Sugiyama, Renata Morita; Tannuri, Uenis
Abstract: Background: To identify prognostic factors for overall survival through the analysis of 132 patients with Wilms tumor followed at a single center, with emphasis on the inferior vena cava/right atrium extension. Methods: Retrospective analysis of overall survival using logistic regression models and including age, sex, clinical features, associated syndromes, comorbidities, tumor size before chemotherapy, stage, presence of metastatic disease and its site, invasion of adjacent structures, inferior vena cava/right atrium extension, laterality, tumor histology, chemotherapy protocol, and radiotherapy as potential risk factors. Results: From January 2000 through November 2021, 132 patients met the inclusion criteria, 64 females and 68 males; 15 (11.4%) patients presented with tumoral extension to inferior vena cava/right atrium and 44 had metastatic disease (33.3%). Based on logistic regression, the factors correlating to a fatal outcome were male sex (p = 0.046), high risk histology (p = 0.036), and the presence of metastatic disease (p = 0.003). None of the patients presenting inferior vena cava/right atrium extension died (p = 0.992). In a specific analysis of metastatic sites, hepatic metastasis alone showed correlation with a fatal outcome (p = 0.001). Conclusion: These results underline the importance of identifying and treating metastatic disease and high-risk tumors. The female gender as a potential driver for a less aggressive disease is a new finding that deserves further investigation. The accurate identification of inferior vena cava/right atrium extension, subsequent preoperative chemotherapy, and resection with a skilled team promoted survival rates of all patients. Level of evidence: II. Highlights: In a specific analysis of metastatic sites, hepatic metastases show a strong correlation with a fatal outcome. None of the patients presenting invasion of inferior vena cava/right atrium died. Based on logistic regression, the factors correlating to a fatal outcome are male sex, presence of metastatic disease and high-risk histology.